Serumen Prop sebagai Faktor Risiko Tuli Konduktif - Ganesha Rahman Hakim; Putu Ristyaning Ayu Sangging; Rani Himayani (Medula, 2023)
Cerumen is a secretion found in the external auditory canal to protect the ear. Wax buildup or cerumen prop is one of the most common ear problems in the world. Deafness is a decrease in hearing even to the inability of the ears to hear. Conductive hearing loss is a type of deafness that occurs due to obstruction in the process of transmitting sound vibrations starting from the auricle to the hearing bone and ends before the vibrations are received by the auditory nerve. The impaction of cerumen on the cerumen prop can inhibit the vibration process so that hearing loss can occur. Because hearing loss occurs in the process of transmitting sound vibrations, therefore this process of hearing loss is classified as conductive hearing loss.